Invariant Solutions for a Class of Perturbed Nonlinear Wave Equations - Waheed A. Ahmed; F. D. Zaman; Khairul Saleh (Mathematics, 2017)
Approximate symmetries of a class of perturbed nonlinear wave equations are computed using two newly-developed methods. Invariant solutions associated with the approximate symmetries are constructed for both methods. Symmetries and solutions are compared through discussing the advantages and disadvantages of each method.